The Strategy of Driving School Principals as Transformational Leaders in Improving Teacher Professionalism and the Quality of Education in Elementary Schools - Ningsih, Susi Widia; Karlimah, Karlimah (Jurnal ini diterbitkan oleh: PGSD FKIP Universitas Muhammadiyah Tasikmalaya, 2024)
This research aims to describe the results of a literature review regarding the strategies of driving school principals as transformational leaders to improve teacher professionalism and the quality of education in elementary schools (SD). This research uses a Narrative Literature Review (NLR) approach with stages: identification of data sources, data selection and analysis process, synthesis and interpretation of findings. The NLR results show that there are three main strategies for driving school principals as transformational leaders in an effort to improve teacher professionalism and the quality of education. The three strategies are, namely, developing programs to increase teacher professionalism in a targeted manner, encouraging a collaborative culture and continuous learning, and providing ongoing encouragement and guidance. These strategies have specificities in terms of programs, which include the approach taken, practical activities, and monitoring and evaluation activities. These strategies encourage increased teacher professionalism and the quality of education in elementary schools. This increase will have an impact on improving the quality of learning and the quality of primary school education outcomes.